Islamic Philanthropy Transformation: Redefining Asnāf Zakat to Strengthen Family Resilience - Gandhung Fajar Panjalu; Salem Mohammad Salem; Salman Al Farisi; Abd. Hadi; Sholihul Huda (Mazahib, 2026)
The traditional distribution of zakat, which focuses on individual charitable aid to the eight categories of recipients (asnÄf), is increasingly seen as less effective at addressing the multidimensional vulnerabilities of modern Muslim families. This socio-legal research underscores the necessity of repositioning zakat from a predominantly consumptive tool into a transformative mechanism for strengthening family resilience. Using Froma Walsh’s Family Resilience Theory as an analytical lens, this study examines the strategic redefinition of the eight asnÄf. The research employs a socio-legal approach, combining normative legal analysis of fiqh texts with an examination of contemporary zakat policies and practices to develop an integrative analytical framework. The findings indicate that redefining the asnÄf enables zakat distribution to move beyond consumptive assistance toward a more integrated and preventive approach that supports multiple dimensions of family resilience, including economic stability, relational cohesion, and value reinforcement. This study proposes a family-centered zakat distribution framework, in which zakat not only fulfills basic needs but also actively strengthens systemic resilience, in line with the maqÄá¹£id al-sharÄ«”˜ah, particularly the protection of progeny (á¸¥ifáº“ al-nasl) and wealth (á¸¥ifáº“ al-mÄl).